Efficacy and Safety of Mesenchymal Stem Cell Transplantation in the Treatment of Autoimmune Diseases (Rheumatoid Arthritis, Systemic Lupus Erythematosus, Inflammatory Bowel Disease, Multiple Sclerosis, and Ankylosing Spondylitis): A Systematic Review and Meta-Analysis of Randomized Controlled Trial - Liuting Zeng; Ganpeng Yu; Kailin Yang; Wang Xiang; Jun Li; Hua Chen (Stem Cells International)
Objective. To evaluate the efficacy and safety of mesenchymal stem cell (MSC) transplantation in the treatment of autoimmune diseases. Methods. The Chinese and English databases were searched for clinical research on the treatment of autoimmune diseases with mesenchymal stem cells. The search time range is from a self-built database to October 1, 2021. Two reviewers independently screened the literature according to the inclusion and exclusion criteria, extracted data, and evaluated the bias of the included studies. RevMan 5.3 analysis software was used for meta-analysis. Results. A total of 18 RCTs involving 5 autoimmune diseases were included. The 5 autoimmune disease were rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), inflammatory bowel disease, ankylosing spondylitis, and multiple sclerosis. For RA, the current randomized controlled trials (RCTs) still believe that stem cell transplantation may reduce disease activity, improve the clinical symptoms (such as DAS28), and the percentage of CD4+CD 25+Foxp3+Tregs in the response group increased and the percentage of CD4+IL-17A+Th17 cells decreased. The total clinical effective rate of RA is 54%. For SLE, the results showed that mesenchymal stem cell transplantation may improve SLEDAI [-2.18 (-3.62, -0.75), P=0.003], urine protein [-0.93 (-1.04, -0.81), P<0.00001], and complement C3 [0.31 (0.19, 0.42), P<0.00001]. For inflammatory bowel disease, the results showed that mesenchymal stem cell transplantation may improve clinical efficacy [2.50 (1.07, 5.84), P=0.03]. For ankylosing spondylitis, MSC treatment for 6 months may increase the total effective rate; reduce erythrocyte sedimentation rate, intercellular adhesion molecules, and serum TNF-α; and improve pain and activity. For multiple sclerosis, the current research results are still controversial, so more RCTs are needed to amend or confirm the conclusions. No obvious adverse events of mesenchymal stem cell transplantation were found in all RCTs. Conclusion. MSCs have a certain effect on different autoimmune diseases, but more RCTs are needed to further modify or confirm the conclusion.